Sports development of Pangkalpinang city viewed from sports development index - Gabriela Raez Sanjaya; Sugiyanto Sugiyanto; M. Furqon Hidayatullah (Kazimierz Wielki University, 2019)
To measure the level of development of community sports can be done by measuring the development of sports through the SDI (Sport Development Index). This study aims to: 1) Describe the results of sports development. 2) Identify the availability of sports open spaces. 3) Identifying the quality and quantity of human resources. 4) Identify the level of community participation in exercise. 5) Measuring the level of physical fitness of the community. 6) Knowing the results of SDI in Pangkalpinang city. This study uses the mixed method method combining two forms of research, namely qualitative and quantitative research. The study sample amounted to 270 people. The sampling technique uses a multistage random sampling method. The results of this study are: 1) Development of sports in the city of Pangkalpinang included in the low category. 2) Index of open space shows a number of 0.363 included in the low category. 3) Index of Human Resources shows a figure of 0.0007 included in the low category. 4) The index of community participation shows that the number of 0.348 is included in the low category. 5) Community Fitness Level shows a number of 0.361 included in the low category. 6) SDI in Pangkalpinang city shows a number of 0.268 included in the low category.